PENGEMBANGAN MODUL AJAR BERBASIS DISCOVERY LEARNING DALAM PEMBENTUKAN KARAKTER DISIPLIN DAN HASIL BELAJAR PADA MATERI BANGUN RUANG SISWA KELAS V GUGUS CIPUKAL AJI GENDOWANG KECAMATAN MOGA KAB. PEMALANG - Ani Purwatiningsih; Munadi; Parijdo (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Mathematics learning in elementary schools, particularly in geometry topics, often faces challenges such as conventional, less varied teaching methods, low student discipline, and a lack of discovery-based teaching modules. This study aims to develop a Discovery Learning-based teaching module to enhance the discipline and learning outcomes of fifth-grade students in the topic of geometry.This research employed a Research and Development (R&D) method using the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The study involved 43 fifth-grade students from the Cipukal Aji Gendowang Cluster, Pemalang Regency. Data were collected through observation, tests, questionnaires, and interviews, and were analyzed using both quantitative and qualitative approaches.The developed teaching module met the validation criteria from content experts (score: 4.2/5) and media experts (score: 4.0/5). A limited trial showed an increase in students' learning outcomes from an average score of 69.06 to 82.15, with 85% of students achieving the minimum mastery criteria. Student discipline also showed significant improvement, as indicated by task completion consistency (87%) and active participation (78%).The Discovery Learning-based module proved effective in enhancing both learning outcomes and student discipline. Its implementation supports the Merdeka Curriculum by emphasizing active and contextual learning.